Natural Resource Management According To The Quran From The Perspective Of Environmental Issues (Al Misbah Interpretation Study) - Efendi, Alhusna; Syahminan, Mhd (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study analyzes the management of natural resources (SDA) according to the Qur'an from the perspective of environmental issues, by referring to Tafsir Al-Misbah by M. Quraish Shihab. Islam views humans as caliphs on earth, who are responsible for maintaining and preserving nature. The principles of justice, balance, and sustainability are the main foundations in the utilization of natural resources. The prohibition against environmental damage and waste of resources is very relevant to modern environmental challenges such as deforestation, pollution, and climate change. This study highlights the importance of wise water management, preservation of flora and fauna, and environmental education as part of the responsibility of mankind. Tafsir Al-Misbah emphasizes that the use of natural resources must be carried out fairly and in balance to ensure the sustainability of nature for future generations. The research method used is a descriptive analytical library study with primary data sourced from the verses of the Qur'an in Tafsir Al-Misbah by M. Quraish Shihab. The research concludes that Islamic teachings on natural resource management, as outlined in Tafsir Al-Misbah, provide strong moral and ethical guidance for addressing current environmental issues. By emphasizing the principles of justice and balance, these teachings support global efforts to achieve environmental sustainability and long-term well-being.